2002
DOI: 10.1002/cne.10372
|View full text |Cite
|
Sign up to set email alerts
|

Direct projections from the cardiovascular nucleus tractus solitarii to pontine preganglionic parasympathetic neurons: A link to cerebrovascular regulation

Abstract: Peripheral or central interruption of the baroreflex or the parasympathetic innervation of cerebral vessels leads to similar changes in regulation of cerebral blood flow. Therefore, we sought to test the hypothesis that the cardiovascular nucleus tractus solitarii, the site of termination of arterial baroreceptor nerves, projects to pontine preganglionic neurons whose stimulation elicits cerebral vasodilatation. The current study utilized both light and electron microscopic techniques to analyze anterograde tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Stimulation of those ganglia leads to cerebral arterial dilatation (Seylaz, J. et al, 1988;Toda, N. et al, 2000b;Toda, N. et al, 2000a) and some reports, which indicate that interruption of the ganglia or their innervation leads to cerebral vasoconstriction (Toda, N. et al, 2000b;Toda, N. et al, 2000a), suggest that they exert a tonic vasodilator influence. Stimulation of the superior salivatory nucleus (SSN), the site of preganglionic neurons that project to the pterygopalatine ganglia and thus influence CBF, also leads to vasodilatation of cerebral vessels (Agassandian, K. et al, 2002). Ganglionic neurons of the pterygopalatine ganglia express a number of potentially vasoactive substances including vasoactive intestinal polypeptide, ACh (implied by the presence of choline acetyltransferase), and nNOS, which would synthesize NO (Yu, J. G. et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulation of those ganglia leads to cerebral arterial dilatation (Seylaz, J. et al, 1988;Toda, N. et al, 2000b;Toda, N. et al, 2000a) and some reports, which indicate that interruption of the ganglia or their innervation leads to cerebral vasoconstriction (Toda, N. et al, 2000b;Toda, N. et al, 2000a), suggest that they exert a tonic vasodilator influence. Stimulation of the superior salivatory nucleus (SSN), the site of preganglionic neurons that project to the pterygopalatine ganglia and thus influence CBF, also leads to vasodilatation of cerebral vessels (Agassandian, K. et al, 2002). Ganglionic neurons of the pterygopalatine ganglia express a number of potentially vasoactive substances including vasoactive intestinal polypeptide, ACh (implied by the presence of choline acetyltransferase), and nNOS, which would synthesize NO (Yu, J. G. et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Our own laboratory has suggested that the pathway may contribute to cerebral vasodilatation during hypertension and thus extend cerebrovascular autoregulation (Talman, W. T. et al, 1994), a suggestion that has been echoed by others in the field (Toda, N. and Okamura, T., 1992). We have shown that arterial baroreceptors are critical for cerebral vasodilatation when blood pressure has been raised beyond the autoregulatory range (Talman, W. T. et al, 1994;Talman, W. T. and Nitschke Dragon, D., 1995b;Talman, W. T. and Nitschke Dragon, D., 2002); that the NTS, where arterial baroreceptor fibers terminate in the central nervous system (Blessing, W. W. et al, 1999;Ciriello, J., 1983;Kalia, M. and Sullivan, J. M., 1982;Torrealba, F. and Claps, A., 1988), projects directly to the SSN (Agassandian, K. et al, 2002); that interruption of function at the level of SSN or pterygopalatine ganglia extends the autoregulatory range during hypertension as does baroreflex interruption (Agassandian, K. et al, 2003;Talman, W. T. and Nitschke Dragon, D., 2000), and that non-selective inhibition of synthesis of NO released by those ganglionic fibers had the same effect (Talman, W. T. and Nitschke Dragon, D., 1995a). These studies further suggest that nitroxidergic nerves projecting from the pterygopalatine ganglion to cerebral blood vessels play a roll in the increase in CBF seen in breakthrough (Talman, W. T. and Nitschke Dragon, D., 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agassandian et al (1) and Boysen et al (4) have shown that direct projections from the cardiovascular nucleus tractus solitarii to the pontine preganglionic parasympathetic neurons, acting through the pterygopalantine ganglia, provide tonic dilatory influences on the cerebral vessels. This may provide a link between changes in central blood volume and arterial baroreflexes to influence cerebral vascular regulation via the extrinsic vascular innervation system (15).…”
Section: Discussionmentioning
confidence: 98%
“…Connection have been found between the Vestibular Nuclei and the Fastigial Nucleus, 2 then to the Rostral Ventrolateral Medulla, 3 followed by vasodilatory connections to the cerebral vessels. 4 Similarly, neurons travel from the Vestibular Nuclei to the Nucleus Tractus Solitarius 5 and then to the Pterygopalatine Ganglion, 6 resulting in cerebral vasodilation. 7 However, the role these connections play with respect to adjustments to posture remains to be determined.…”
mentioning
confidence: 99%